2003
DOI: 10.1007/s00248-002-2029-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Eubacterial 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductases from Natural Populations of Actinomycetes

Abstract: Three natural populations of actinomycetes were investigated by PCR for the presence of type I 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG CoA), a gene associated with isoprenoid biosynthesis. The populations were obtained from an agricultural site (69 isolates), a coastal salt marsh (220 isolates), and a desert soil (96 isolates). A set (34) of standard actinomycete reference strains were also investigated. The target gene was only detected in 5 of the 419 actinomycetes screened, which represented 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Actinomycetes isolated from marine invertebrates have also been shown to produce previously reported HIs [45 ,46,47], however the phylogenetic relationships of these strains are unknown because of limited 16S sequence availability. A 2003 study by Sigmund et al [48] provided the first evidence that marine strains may be enriched in HI secondary metabolite production with the observation that all four hmgr positive strains, out of 385 screened, were from marine sources. Similarly, a 2010 study by Khan et al [35 ] identified six actinomycete strains containing the hmgr gene out of 523 marine-derived strains screened.…”
Section: Hi Producing Strains From the Marine Environmentmentioning
confidence: 97%
“…Actinomycetes isolated from marine invertebrates have also been shown to produce previously reported HIs [45 ,46,47], however the phylogenetic relationships of these strains are unknown because of limited 16S sequence availability. A 2003 study by Sigmund et al [48] provided the first evidence that marine strains may be enriched in HI secondary metabolite production with the observation that all four hmgr positive strains, out of 385 screened, were from marine sources. Similarly, a 2010 study by Khan et al [35 ] identified six actinomycete strains containing the hmgr gene out of 523 marine-derived strains screened.…”
Section: Hi Producing Strains From the Marine Environmentmentioning
confidence: 97%
“…Orthologs of these six genes, arranged in the exact same order, are found in the biosynthetic gene cluster of furaquinocin (25), naphterpin (26), terepenticin (27), and BE 40644 (28). S. anulatus, there- fore, is one of the rare Streptomyces species that possesses the genes of the mevalonate pathway, a feature limited to Ïł1% of the strains of this genus (29). Directly adjacent to the genes of the mevalonate pathway, a gene designated ppzP was identified (Fig.…”
Section: Cloning Of a Biosynthetic Gene Cluster For Prenylatedmentioning
confidence: 99%
“…Similarly PCR primers targeting aminoglycoside phosphotransferase genes (APH) were used to detect resistance genes associated to these biosynthetic pathways [26]. In a different approach the occurrence of isoprenoid biosynthesis pathways in actinomycetes was studied with PCR primers designed for the 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG CoA) [25]. For that reason, the combined data derived from the chemotaxonomic and molecular fingerprinting methods and the detection of biosynthetic systems such as PKS-I, PKS-II, NRPS, APH and HMG CoA have been applied to evaluate the diversity of this microbial community from a different perspective, in terms of the richness in these biosynthetic pathways.…”
Section: Introductionmentioning
confidence: 99%